MEDIATION MODEL OF SELF-EFFICACY ON STUDENT ENTREPRENEURIAL INTEREST (International Journal of Innovative Technologies in Economy, 2023)
Unemployment in Indonesia presents a pressing social issue that demands attention and resolution. This research aims to enhance the entrepreneurial interest of Indonesian university graduates as a potential solution to the unemployment problem. The study primarily focuses on understanding the role of the family environment in shaping individual character and as a platform for instilling entrepreneurial values. Entrepreneurship education is considered a pivotal factor in developing entrepreneurial skills, which, in turn, stimulate the growth of entrepreneurial interest, spirit, and higher self-efficacy levels among students. The findings of this research provide compelling evidence that family background and entrepreneurship education significantly contribute to boosting students' entrepreneurial interest. This plays a vital role in addressing the unemployment challenge. By nurturing entrepreneurial aspirations among graduates, the study promotes entrepreneurship as a viable career choice in Indonesia. Consequently, it aids in curbing unemployment rates by empowering graduates with the skills and mindset needed for entrepreneurial success. This research underscores the potential for family influence and entrepreneurship education to serve as effective tools in encouraging entrepreneurial interest among students, contributing to a more sustainable solution to unemployment.